PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMP IT KHAZANAH - suraidah, suraidah; syafi'i, imam; ekowati, endang (UNISAN JURNAL, 2023)
The aim is to describe the PAI learning process at SMP IT Khazanah Kebajikan Palembang by planning, implementing and learning the PAI at SMP IT Khazanah Kebajikan Palembang. This research includes empirical qualitative research using a field research approach (field evaluation research). There are several methods of collecting data, namely observation, interviews and documentation. As for the steps taken in analyzing, namely by collecting data, data reduction, data display (presentation of data), verification (drawing conclusions). The results of this study prove that the internal psychological characteristics of students in PAI learning are very diverse, especially from the point of view of their classification. Students from superior classes have good psychological characteristics and support a good learning process. While students from the regular class are below students from superior classes in terms of psychological characteristics. PAI learning planning is administratively and procedurally carried out by PAI teachers which includes annual programs, semesters, syllabus and learning implementation plans. But there are still a number of things that need to be improved, especially in designing the components of the learning process. The implementation of the PAI learning process at SMP IT Khazanah Kebajikan Palembang went well and was procedural. However, there needs to be improvement in the implementation of apperception, the learning methods used, and the deepening and broadening of learning materials. The learning carried out by PAI teachers includes learning processes and outcomes. the process is intended to assess and measure the level of effectiveness of the learning components in a comprehensive manner. And the results aim to measure the learning progress achieved by students after completing learning in one basic competency or several basic competencies